An Overview of Optical Burst Switching Network Routing Methods (International Journal of Food and Nutritional Sciences, 2022)
In recent years, networking has expanded very quickly. Internet use is rapidly growing, and there are more and more bandwidth-hungry apps like multimedia and m-commerce services available. In the foreseeable future, OBS is the most likely choice for multimedia apps that are hungry. Burst contention, however, is a drawback of this well-liked method. OBS must be successful in order to be a viable alternative to burst conflict. The major contribution of this study is a review of the state-of-the-art optical burst switched networks routing techniques developed by researchers to avoid burst contention. Directing frameworks are straightforward and economical in light of the fact that they are carried out in the space. The paper likewise features the significance of directing as a down to earth substitute for different ways to deal with adapting to burst blockage. It also highlights the key distinctions between optical burst switching network conflict avoidance methods and congestion resolution approaches. This review, we think, will benefit many optical burst switching researchers working on route optimization methods to manage burst contention